2019
DOI: 10.5005/jp-journals-10071-23118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Extended Spectrum â-lactamase and Carbapenemase Producing Klebsiella pneumoniae from a Tertiary Care Hospital

Abstract: Objective The extended-spectrum beta-lactamase (ESBL) and carbapenemase producing gram-negative bacteria among the members of Enterobacteriaceae are of major health concern globally. The present study was carried out to determine proportion and genetic characterization of ESBL and carbapenemase producing Klebsiella pneumoniae strains isolated from intensive care units of a tertiary care hospital. Materials and methods A total of 250 non-duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 78%
“…Bhaskar et al 33 treated Klebsiella pneumoniae with Cefotaxime (30 µg). He found wrinkled with roughsurfaced bacterial cells when examining with SEM.…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae have acquired carbapenemases, which are capable of breaking down most β-lactams, including carbapenems, and confer resistance to these drugs. Reports indicate that carbapenemase- producing Enterobacteriaceae isolates are increasing in number in the last few years [39].…”
Section: Discussionmentioning
confidence: 99%